Carboplatin and programmed death‐ligand 1 blockade synergistically produce a similar antitumor effect to carboplatin alone in murine ID8 ovarian cancer model. Issue 2 (24th November 2017) - Zhu, Xinxin; Xu, Jia; Cai, Han; Lang, Jinghe
Abstract: Aim: In advanced, platinum resistant or refractory ovarian cancer (OC), the therapeutic efficacy of carboplatin is controversial. Although anti‐programmed death‐1/programmed death‐ligand 1 (PD‐1/PD‐L1) pathway blockages show great potential in cancer treatment, the antitumor effect of single anti‐PD‐L1 pathway monoclonal antibody (mAb) is not obvious in advanced or some poorly immunogenic tumors, including OC. We compared the effects of single or combined carboplatin and anti‐PD‐L1 mAb treatments and explored the possible antitumor mechanisms in a murine ID8 OC model. Methods: C57BL/6 mice with established peritoneal ID8 OC were intraperitoneally injected with single or combined carboplatin and anti‐PD‐L1 mAb. The formation time of ascites and their overall survival were recorded. The compositions of tumor‐associated immune cells were analyzed by flow cytometry. Results: A single treatment of carboplatin and combined carboplatin/PD‐L1 mAb induced a strong anti‐ascites response. Mice treated with carboplatin presented the longest overall survival, followed by the combined remedy. Mechanistic investigation of the tumor microenvironment revealed that carboplatin and carboplatin/PD‐L1 mAb increased antitumor effector CD4 +, CD8 + T cells and decreased immunosuppressive regulatory T and myeloid suppressor cells, giving rise to remarkably higher ratios of effector CD4 +, CD8 + T cells to regulatory T cells and myeloid suppressor cells in the peritoneal cavity. Conclusions: To our knowledge, this is the first report to compare the antitumor effect and potential mechanisms between carboplatin, PD‐L1 mAb and their combination strategies in a murine ID8 OC model. The results of this study may deepen our understanding of OC and aid future preclinical experiments or clinical trials.